Clinical features and practice patterns of treatment for adrenal crisis: a nationwide cross-sectional study in Japan. Issue 3 (March 2017) - Ono, Yosuke; Ono, Sachiko; Yasunaga, Hideo; Matsui, Hiroki; Fushimi, Kiyohide; Tanaka, Yuji
Abstract : Context: Adrenal crisis is an endocrine emergency that requires prompt diagnosis and treatment. However, the clinical features and practice patterns of treatment for adrenal crisis are not completely understood. Objective: To investigate patient characteristics, comorbidities and treatments of adrenal crisis. Methods: We conducted a cross-sectional study of patients who received intravenous glucocorticoids for adrenal crisis at admission from 1 July 2007 to 31 March 2014, using a national inpatient database in Japan. Results: Among approximately 34 million inpatients in the database, we identified 799 patients diagnosed with adrenal crisis and coexisting primary or secondary adrenal insufficiency at admission. The median (interquartile range) age was 58 (28–73) years, and the overall in-hospital mortality was 2.4% (19 of 799 patients). The most common comorbidity at admission was infections excluding pneumonia and gastroenteritis (15.0%). There were 68 (8.5%) patients with gastroenteritis, and no deaths occurred among these patients. The patients with secondary adrenal insufficiency showed significantly higher proportions of admission to ICU, extracellular fluid resuscitation, insulin therapy and catecholamine use than the patients with primary adrenal insufficiency. There were no significant between-group differences in mortality rate and variation in intravenous glucocorticoids (short-acting glucocorticoid, hydrocortisone; moderate-acting glucocorticoid, prednisolone or methylprednisolone; long-acting glucocorticoid, dexamethasone or betamethasone). Of the 19 dead patients, 15 were aged above 60 years, 12 had impaired consciousness at admission and 13 received insulin therapy. Conclusions: Clinicians should be aware that older patients with impaired consciousness and diabetes mellitus are at relatively high risk of death from adrenal crisis.